2011
DOI: 10.2147/ijn.s25268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the levofloxacin release characters from a rabbit foldable capsular vitreous body

Abstract: The authors have manufactured a novel rabbit foldable capsular vitreous body (FCVB). The aim of this study was to determine whether this rabbit FCVB can release levofloxacin in vitro and in vivo, and to evaluate the release characteristics. In vitro, the rabbit FCVB with levofloxacin 500 μg/mL was immersed in cups of modified Franz diffusion cells. Following this, 200 μL of liquid was aspirated at intervals from 10 minutes to 24 hours. In vivo, the FCVB with levofloxacin was implanted into the right eyes of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…In our previous study, we reported that the release values of the FCVB with 500 lg/mL levofloxacin in normal eyes were 132, 50, 39, 11, and 15 ng/mL on days 1, 7, 14, 28, and 56, respectively. 26 In our study, we found that the values with 625 lg/mL levofloxacin in endophthalmitis eyes were 42, 31, 12.5, 5.6, 2.5, and 0.6 ng/mL on days 1, 3, 5, 10, 20, and 30, respectively. Although similar release tendency appeared, release values in normal eyes were bigger than those in endophthalmitis ones probably due to inflammation.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…In our previous study, we reported that the release values of the FCVB with 500 lg/mL levofloxacin in normal eyes were 132, 50, 39, 11, and 15 ng/mL on days 1, 7, 14, 28, and 56, respectively. 26 In our study, we found that the values with 625 lg/mL levofloxacin in endophthalmitis eyes were 42, 31, 12.5, 5.6, 2.5, and 0.6 ng/mL on days 1, 3, 5, 10, 20, and 30, respectively. Although similar release tendency appeared, release values in normal eyes were bigger than those in endophthalmitis ones probably due to inflammation.…”
Section: Discussionsupporting
confidence: 45%
“…42 Therefore, FCVB results also may have implications in the treatment of important retinal diseases that need drug and vitreous substitutes, such as age-related macular degeneration, proliferative vitreoretinopathy, and proliferative diabetic retinopathy. This work, along with our other reports regarding the FCVB, [21][22][23][24][25][26][27][28][29][30]42 give an example of how to make the product from bench to bedside, including idea, craft, animal model, producing standard, technical reports from government, clinical trails (exploratory, multiple centers), and marketing. Based on this study, we will apply for a new clinical trial to test the combined function of FCVB.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the FCVB capsule, mini-apertures of 300 nm were detected via the scanning electron microscope1755 and in our previous studies, we noted that these mini-apertures can slowly release micromolecular substances, such as dexamethasone sodium phosphate56, 5-fluorouracil (5-Fu)57 and siRNA-PKCα55. Therefore, the thin capsule membrane was highly oxygen permeable due to the mini-apertures.…”
Section: Discussionmentioning
confidence: 96%